Influence of deposition rate and substrate temperature on structure and optical features of NiO thin film - Oberemok, O.S.; Sabov, T.M.; Lisovskyy, I.P.; Khacevych, I.M.; Gudymenko, O.Yo.; Nikirin, V.A.; Voitovych, M.V. (Functional Materials, 2016)
Nickel oxide thin films were prepared by direct-current magnetron sputtering method at different deposition rates on unheated and heated substrates. It was shown that the deposited films are the dense arrays of nanowhiskers with the rhombohedral crystalline structure for the unheated substrate and with the face centered cubic structure for the heated substrate. Surface morphology of films consists of nanocrystalline randomly oriented grains. Increasing of the deposition rate and/or the substrate temperature lead to decrease of the film porosity and enlarge of nanocrystals. The maximum oxidation state of the deposited films is observed near the surface.